Microbiological and physico-chemical quality of water from beveragers of Uberlândia Federal University, Campus Santa Mônica: Calidad del água de bebederos de la Universidade Federal de Uberlândia - de Oliveira Silva Fernandes Correia, Gabriela; Moura Bertolino, Sueli; Alves Baffi, Milla (Revista Brasileira de Ciência, Tecnologia e Inovação, 2023)
This study evaluated the water quality of drinking fountains in the buildings 1B and 5RA at the Santa Mônica campus, Federal University of Uberlândia, monitoring that is part of the institution's Water Safety Plan. The water quality was investigated through bacteriological analysis and physicochemical parameters. The analyses were during 12 weeks in a total of 72 samples. In the bacteriological analysis, none of the samples showed growth of coliforms, being this parameter in accordance to the legislation. In the physicochemical analysis, an average pH of 5.62 and 5.44 was obtained in 1B and 5RA buildings, respectively. In 1B, the color showed an average of 6.85 uC, with six samples showing values slightly above the limit. The other parameters were in accordance to the standards, with average values for block 1B of: turbidity - 0.18 NTU, conductivity - 64.55 us cm-1 and dissolved solids - 43.89 mg L-1 and for 5RA were of: color - 2.10 uc, turbidity - 0.14 NTU, conductivity - 52.70 us cm-1 and dissolved solids - 35.84 mg L-1. Regarding metals, only one sample from 1B presented values of iron, chromium and nickel above the limit. The results indicate the potability and the security of the evaluated water in terms of microbiological, toxicological and organoleptic indicators.